TANTANGAN INDONESIA DALAM MEWUJUDKAN PERTUMBUHAN EKONOMI YANG KUAT DAN PEMBANGUNAN EKONOMI BERKELANJUTAN MELALUI INDONESIA GREEN GROWTH PROGRAM OLEH BAPPENAS - Rany, Alya Prastika; Farhani, Salsabila Azkia; Nurina, Vidya Rizky; Pimada, Laila Masruro (EP FEB UNS, 2020)
The Ministry of National Development Planning of Indonesia established the Green Growth Program in order to address the problems of climate change caused by economic activities. Along with the Global Green Growth Institute (GGGI), the idea of Green Growth becomes important to discuss due to the nation’s priority for strong economic growth and sustainable development. Green economic growth tries to develop its program in several ways, namely the development of bankable projects, increasing green economy investment in several sectors, and designing creative and innovative economic instruments and policies. In addition, the Green Growth Program has several programs implemented, namely energy programs, energy landscape programs, special economic zones (KEK) programs, and climate fund programs. In its implementation, yet the Green Growth Program encounters many challenges. The challenges faced relate to human resources, institutional design, and trade offs faced by the state. With a qualitative approach the descriptive method the researcher explains the importance of the Green Growth Program and the challenges faced in carrying out these programs. Keywords: Green Growth; Economic growth; Sustainable Development.